Gradual Increase of High Mobility Group Protein B1 in the Lungs after the Onset of Acute Exacerbation of Idiopathic Pulmonary Fibrosis - Ebina, Masahito; Taniguchi, Hiroyuki; Miyasho, Taku; Yamada, Shingo; Shibata, Naoko; Ohta, Hiromitsu; Hisata, Shu; Ohkouchi, Shinya; Tamada, Tsutomu; Nishimura, Hidekazu; Ishizaka, Akitoshi; Maruyama, Ikuro; et al. (Pulmonary Medicine, 2011)
The pathogenesis of acute exacerbation of idiopathic pulmonary fibrosis (IPF) remains to be elucidated. To evaluate the roles of inflammatory mediators in acute exacerbation, the concentrations of high mobility group protein B1 (HMGB1), a chief mediator of acute lung injury, and 18 inflammatory cytokines were measured in the bronchoalveolar lavage fluid, serially sampled from seven IPF patients after the onset of acute exacerbation. HMGB1 gradually increased in the alveolar fluid after the onset of acute exacerbation, in positive correlation with monocytes chemotactic protein-1 (MCP-1), a potent fibrogenic mediator. In the lung tissues of eight IPF patients autopsied after acute exacerbation, intense cytoplasmic staining for HMGB1 was observed in the alveolar epithelial cells in alveolar capillary augmented lesions, where the capillary endothelial cells remarkably reduced the expression of thrombomodulin, an intrinsic antagonist of HMGB1. These results suggest pathogenic roles for HMGB1 and MCP-1 in the late phase of acute exacerbation of IPF.